Influence of the Polymeric Matrix on the Optical and Electrical Properties of Copper Porphine-Based Semiconductor Hybrid Films - Sánchez Vergara, Maria Elena; Hernández Méndez, Joaquín André; González Verdugo, Daniela; Giammattei Funes, Isabella María; Lozada Flores, Octavio (MDPI, 2023)
In this study, we assessed the electrical and optical behavior of semiconductor hybrid films fabricated from octaethyl-21H,23H-porphine copper (CuP), embedded in polymethylmethacrylate (PMMA), and polystyrene (PS). The hybrid films were characterized structurally and morphologically using infrared spectroscopy (IR), atomic force microscopy (AFM), scanning electron microscopy (SEM), and X-ray diffraction (XRD). Subsequently, the PMMA:CuP and PS:CuP hybrid films were evaluated optically by UV–vis spectroscopy, as well as electrically, with the four-point collinear method. Hybrid films present a homogeneous and low roughness morphology. In addition, the PS matrix allows the crystallization of the porphin, while PMMA promotes the amorphous structure in CuP. The polymeric matrix also affects the optical behavior of the films, since the smallest optical gap (2.16 eV) and onset gap (1.89 eV), and the highest transparency are obtained in the film with a PMMA matrix. Finally, the electrical behavior in hybrid films is also affected by the matrix: the largest amount of current carried is approximately 0.01 A for the PS:CuP film, and 0.0015 A for the PMMA:CuP film. Thanks to the above properties, hybrid films are promising candidates for use in optoelectronic devices.
Keywords: Polymethylmethacrylate; Polystyrene; Porphine; Hybrid film; Optical properties; Electrical behavior